Impact of topical anti-inflammatory therapy on morpho-functional characteristics of epidermal barrier. Optimization of atopic dermatitis treatment schedules - L. S. Kruglova; D. D. Petrunin (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
In this literature review data regarding impact of topical therapy with topical corticosteroids (TCS) and tacrolimus ointment on morpho-functional characteristics of epidermal barrier is analyzed. Whereas TCS has profound negative impact on nearly all epidermal barrier parameters, including epidermal structure and thickness, integrity and cohesion of stratum corneum, protease activity, hydration, pH, differentiation, lipid lamellae structure etc., tacrolimus ointment (Protopic®) exerts positive effect on the majority of the aforementioned parameters, thus allowing to compensate deleterious effect of TCS. These data allow defining recommendations upon optimization of topical therapy of atopic dermatitis with stepwise switching from TCS to Protopic® ointment.